1994
DOI: 10.1007/bf02428309
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of low back pain in 1398 Swiss conscripts between 1985 and 1992

Abstract: The two objectives of this study, based on a sample of 1398 Swiss army conscripts born in 1966 who participated in a first study in 1985, were to measure the prevalence of low back pain (LBP) at age 26 years and its incidence between 19 and 26 years and to analyze the relationship between LBP and occupational, nonoccupational, or physical risk factors. The lifetime prevalence of LBP at age 26 was 69.1% and the incidence of LBP between 19 and 26, 44.7%. A history of LBP or a pathological physical examination re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This figure is similar to the data reported in Saudi Arabia (51.6%) 17 . This prevalence rate confirms and is consistent with rates of LBP reported in other community‐ and primary health care‐based investigations in other countries, including: Denmark 17 (51%); Australia 10 (57%); the UK (Palmer 5 49%, and Walsh 7 57%); China 18 (54.4%); the US 21 (71%); Switzerland 22 (69%); and Canada 23 (67.7%). The inquiry about LBP in the present study was similar to that which had been used in earlier surveys 1,7 .…”
Section: Discussionsupporting
confidence: 90%
“…This figure is similar to the data reported in Saudi Arabia (51.6%) 17 . This prevalence rate confirms and is consistent with rates of LBP reported in other community‐ and primary health care‐based investigations in other countries, including: Denmark 17 (51%); Australia 10 (57%); the UK (Palmer 5 49%, and Walsh 7 57%); China 18 (54.4%); the US 21 (71%); Switzerland 22 (69%); and Canada 23 (67.7%). The inquiry about LBP in the present study was similar to that which had been used in earlier surveys 1,7 .…”
Section: Discussionsupporting
confidence: 90%
“…The results of specific research into work related disability related to occupational low back pain in soldiers have tended to mirror and confirm civilian findings. Risk factors have been identified as female gender, age, infrequent aerobic exercise, longer length of service, higher levels of daily work worries, no support from others, higher levels of ergonomic exposure, stressful work and greater perceived effort at work (20)(21)(22). Lower levels of innovation, involvement and line management support were associated with symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…As stated above it is the most common injury sustained during military training and at work. Studies from Finland, Denmark and Switzerland have studied the impact of low back pain on military service (22,23,24) and concluded that the main factors in the aetiology of this condition were lifting, carrying, standing for long periods, twisting and heavy work. Long term follow up (22,23) demonstrated that the frequency of attacks of low back pain increased during military service and was a major cause of time off work after leaving.…”
Section: Low Back Painmentioning
confidence: 99%